PERBANDINGAN PLAYFAIR CIPHER DENGAN 3D PLAYFAIR CIPHER PADA PENGAMANAN CITRA - Sukmawati, Rika Ayu; Riski, Abduh; Kamsyakawuni, Ahmad (Majalah Ilmiah Matematika dan Statistika, 2021)
The development of sending messages that are increasingly easy and sophisticated makes it easier for third parties to access or sabotage the contents of the message, so we need a science called cryptography to secure the message. This research is to secure the message on image encoding using Playfair Cipher and 3D Playfair Cipher. The process of encryption and decryption on Playfair Cipher uses two-letter pairs (bigram), while in 3D Playfair Cipher uses three-letter pairs (trigrams). The encryption process uses Playfair Cipher and 3D Playfair Cipher to produce a different image cipher with plain image visually. In the decryption process, the cipher image returns into the plain image using Playfair Cipher and 3D Playfair Cipher. Histogram analysis, NPCR, and UACI are used to see the difference between ordinary images and password images using Playfair Cipher and 3D Playfair Cipher. The average results of histogram analysis that shows safe based on research data are 14061,483 using 3D Playfair Cipher, the average NPCR results that show safe based on research data are 99.2% using Playfair Cipher, and the average UACI results showing safe based on research data is 29.1% using 3D Playfair Cipher. The results of the study indicate that the proposed method can be used to secure the message.